Impact strength of 16Cr-20Ni-2Mo-Ti austenite steel under shockwave load in sub-microsecond range - Garkushin, Gennady V; Savinykh, Andrey S.; Razorenov, Sergey V.; Atroshenko, S. A. (Russian physics journal)
The paper focuses on the measurements of the free surface displacement of 16Cr-20Ni-2Mo-Ti reactor vessel steel specimens at room temperatures and higher. It is shown that the mechanical inhomogeneity of the steel structure leads to a significant spread in values of the Hugoniot elastic limit and spallation strength. The experiments show that the high-pressure hexagonal close packed structure does not appear after the steel specimen compression.